2008
DOI: 10.3748/wjg.14.1510
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotypes in southwest Iran: Molecular, serological and clinical outcomes

Abstract: AIM:To investigate the associations of hepatitis B virus (HBV) genotype with HBeAg and anti-HBe status, alanine aminotransferase (ALT) levels and HBV-DNA detection in different groups of HBV-infected patients in southwest Iran. METHODS:A total of 89 HBsAg-positive serum samples were collected from the same number of patients. All sera were then investigated to determine HBV DNA and serological markers. For all the polymerase chain reaction (PCR)-positive samples, biochemical, histopathological assays and genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38). As all reports from Iran showing that genotype D is the only detectable genotype in all clinical forms of HBV infection in this country (41, 42). It is expected that HDV genotype I was detected as predominant genotype in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38). As all reports from Iran showing that genotype D is the only detectable genotype in all clinical forms of HBV infection in this country (41, 42). It is expected that HDV genotype I was detected as predominant genotype in this study.…”
Section: Discussionsupporting
confidence: 57%
“…In this regard, patients with detectable DNA and normal ALT levels are said to be in the immunotolerant phase [38]. In contrast to our study, 65.5% of the Iranian patients with chronic hepatitis B showed ALT levels that were higher than normal values in Iran [39]. Persistently normal or only slightly elevated ALT levels in blood were a characteristic finding in HBV-DNA-negative samples.…”
Section: Discussioncontrasting
confidence: 50%
“…HBV and HCV genotyping was performed using polymerase chain reaction-restriction fragment length polymorphisms and genotype specific primers respectively, as previously described (15, 16). α-fetoprotein was detected by commercial quantities Enzyme linked Immunosorbent Assay kits (ConAg, Sweden) according to the manufactures' instructions.…”
Section: Methodsmentioning
confidence: 99%